Far-infrared synergistic dispersion bio-based composite regenerating agent, preparation method thereof and asphalt heat regeneration method
Patent Information
- Application Number
- CN202611321625.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
然而,由于橡胶粉表面能较高、颗粒间接触面积大,在油相或沥青中极易发生团聚,团聚不仅导致分散不均,还会造成局部过度吸油,使橡胶粉过度溶胀而刚化,进一步劣化低温性能
[0027]1、本发明利用生物基油和环氧植物油类增塑剂的双亲结构,在极性陶瓷粉表面与非极性橡胶粉/基质沥青之间构建分子桥接式界面耦合结构,从而实现了多相组分的均匀稳定分散,避免了因团聚导致的局部过度吸油和低温刚化,保证了再生沥青的高低温性能。
Smart Images

Figure CN123004153A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering asphalt material recycling technology, and in particular to a far-infrared synergistic dispersion bio-based composite regenerator and its preparation method and asphalt thermal recycling method. Background Technology
[0002] During mixing, construction, and long-term service, asphalt pavements are continuously subjected to heat, oxygen, ultraviolet radiation, moisture, and traffic loads. This leads to the loss of lightweight components, an increase in oxidizing polar components, and a rearrangement of the colloidal structure in the asphalt binder. Macroscopically, this manifests as decreased penetration and ductility, increased viscosity and stiffness, reduced low-temperature stress relaxation capacity, and decreased water resistance at the asphalt-aggregate interface. For SBS-modified asphalt, aging is also accompanied by SBS chain segment damage, polymer phase instability, and elastic network degradation.
[0003] Existing regenerants mainly have the following problems:
[0004] 1. Bio-based recycled oil can replenish the light components lost in aged asphalt and improve its fluidity and low-temperature flexibility. However, simply increasing the bio-based oil content often leads to a significant decrease in the high-temperature structural support and elastic recovery capacity of the asphalt. To address this, existing technologies introduce rubber powder to absorb oil and swell, forming an elastic network structure to enhance high-temperature resistance to deformation. However, due to the high surface energy and large interparticle contact area of rubber powder, it is prone to agglomeration in the oil phase or asphalt. Agglomeration not only leads to uneven dispersion but also causes localized excessive oil absorption, resulting in excessive swelling and stiffening of the rubber powder, further deteriorating its low-temperature performance.
[0005] 2. Existing asphalt hot recycling usually relies on external heat conduction for heating. The heat source is transferred from the surface of the mixture to the interior, which easily creates a temperature gradient of external heat and internal cold, resulting in low heating efficiency, long heating time, and the outer layer of asphalt is prone to accelerated aging due to local overheating. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by providing a far-infrared synergistic dispersion bio-based composite regenerator with uniformly dispersed components, its preparation method, and an asphalt thermal regeneration method. This method can reduce the internal and external temperature difference during the thermal regeneration process while also taking into account the high and low temperature performance of the regenerated asphalt.
[0007] To achieve the above-mentioned objectives, the far-infrared synergistic dispersion bio-based composite regenerator and its preparation method, along with the asphalt thermal regeneration method, employ the following technical solutions:
[0008] A far-infrared synergistic dispersion bio-based composite regenerator comprises the following components in parts by weight: 39-60 parts by weight of bio-based regenerated oil, 3-16 parts by weight of plasticizer, 0.6-2.4 parts by weight of anti-aging agent, 0.6-2.4 parts by weight of far-infrared ceramic powder, 13-36 parts by weight of matrix asphalt, and 2-14 parts by weight of rubber powder; wherein the plasticizer includes epoxy vegetable oil plasticizer.
[0009] Preferably, the epoxy vegetable oil plasticizer is selected from one or more of epoxidized soybean oil, epoxidized linseed oil, and epoxidized fatty acid methyl esters.
[0010] Preferably, the plasticizer further includes a cold-resistant ester plasticizer, which is selected from one or more of acetylated tributyl citrate, tributyl citrate, dioctyl sebacate, and dioctyl adipate; the epoxy vegetable oil plasticizer accounts for 30-100% of the total mass of the plasticizer.
[0011] Preferably, the bio-based recycled oil is selected from one or more of tall oil-based bio-based oils, waste edible oil modified products, vegetable oils, vegetable oil fatty acid esters, and biomass pyrolysis oil modified products; the tall oil-based bio-based oil is selected from one or more of tall oil, distilled tall oil, tall oil fatty acids, tall oil pitch, and tall oil pitch modified products.
[0012] Preferably, the far-infrared ceramic powder is selected from one or more of the following minerals: silicon dioxide, aluminum oxide, zirconium oxide, titanium dioxide, iron oxide, manganese oxide, magnesium oxide, calcium oxide, cerium oxide, zircon sand, feldspar, maifanite, cordierite, and spinel.
[0013] Preferably, the anti-aging agent includes a primary antioxidant and a secondary antioxidant; the primary antioxidant is a hindered phenolic antioxidant, and the secondary antioxidant is a phosphite antioxidant and / or a thioester antioxidant.
[0014] A method for preparing a far-infrared synergistic dispersion bio-based composite regenerator includes the following steps:
[0015] S1. Premix rubber powder with far-infrared ceramic powder to obtain composite powder;
[0016] S2. Mix a portion of the bio-based recycled oil with a portion of the plasticizer to form a pre-dispersion medium;
[0017] S3. Add the composite powder to the pre-dispersion medium and pre-dispersion together to obtain a dispersion slurry;
[0018] S4. Take the remaining amount of bio-based recycled oil, the remaining amount of plasticizer and anti-aging agent, mix them, and then add them to the dispersion slurry and mix well to obtain the bio-based functional dispersion mother liquor.
[0019] S5. After heating the base asphalt, mix it with the bio-based functional dispersion mother liquor and keep it warm until the rubber powder has completed oil absorption and swelling. The rubber powder absorbs oil and swells to 1.2 to 1.8 times its original particle size to obtain a far-infrared synergistic dispersion bio-based composite regenerator.
[0020] Preferably, in step S2, the amount of bio-based recycled oil added accounts for 5-20% of its total mass, the amount of plasticizer added in step S2 accounts for 30-60% of the total mass of plasticizer, and the plasticizer added in step S2 is an epoxy vegetable oil plasticizer.
[0021] Preferably, in step S1, the mixture is stirred at a speed of 300-1000 r / min for 5-30 min to complete the premixing.
[0022] The temperature of the pre-dispersed medium in step S2 is 50℃~90℃;
[0023] In step S3, the mixture is stirred at a speed of 800–2500 r / min for 20–60 min to complete the co-pre-dispersion.
[0024] In step S5, the base asphalt is heated to 160-180°C, and the bio-based functional dispersion mother liquor is slowly added. The mixture is then stirred or sheared at 140-180°C for 10-80 minutes and kept at 140-180°C for 10-60 minutes.
[0025] A method for thermal recycling of asphalt includes the following steps: adding the far-infrared synergistic dispersion bio-based composite regenerator as described in any one of claims 1 to 6 to aged asphalt material at a mass ratio of 2.5% to 10%, then heating it with a far-infrared heating device with a main emission band of 8 to 14 μm, stirring the aged asphalt material and the far-infrared synergistic dispersion bio-based composite regenerator evenly under heating conditions of 120°C to 170°C, and completing the recycling under continuous stirring conditions.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0027] 1. This invention utilizes the amphiphilic structure of bio-based oil and epoxy vegetable oil plasticizers to construct a molecular bridging interface coupling structure between the polar ceramic powder surface and the non-polar rubber powder / base asphalt, thereby achieving uniform and stable dispersion of multiphase components, avoiding local excessive oil absorption and low-temperature stiffening caused by agglomeration, and ensuring the high and low temperature performance of recycled asphalt.
[0028] 2. The present invention follows a specific sequence of premixing rubber powder and far-infrared ceramic powder and pre-dispersing them together with the oil phase, so that the far-infrared ceramic powder is pre-enriched at the cross-linking shear interface between the bio-based oil phase and the rubber powder, forming a far-infrared ceramic microparticle spacer layer, which physically isolates the rubber particles and effectively inhibits their aggregation.
[0029] 3. Far-infrared ceramic powder is enriched at the interface of rubber particles to form far-infrared radiation micro-regions, thereby achieving internal heating, reducing the temperature difference between the inside and outside, overcoming the limitations of the external heat conduction caused by the temperature difference between the outside and inside, greatly improving heating efficiency, and avoiding the accelerated aging of the outer asphalt due to local overheating.
[0030] 4. This invention promotes the accelerated penetration and diffusion of bio-based regenerated oil into the interior of rubber powder through heating in the far-infrared radiation micro-region, thereby further swelling and activating the rubber powder and forming a stable synergistic swelling network. Attached Figure Description
[0031] Figure 1 A schematic diagram illustrating the mechanism of synergistic dispersion of ceramic powder and rubber powder and the formation of far-infrared secondary swelling network;
[0032] Figure 2 A comparison chart of far-infrared heating efficiency and basic physical properties;
[0033] Figure 3 A comparison chart of the high-temperature rheological properties of MSCR;
[0034] Figure 4 A comparison chart of the low-temperature rheological properties of BBR;
[0035] Figure 5 A comparison chart of BBS interface adhesion performance;
[0036] Figure 6 This is a comparison chart of the synergistic effect between the measured values and the theoretical values obtained by simple superposition in Example 1;
[0037] Figure 7 Flowchart for BBS fracture surface image quantization and failure mode determination;
[0038] Figure 8 Figure 1 shows the effect of co-predisposition of ceramic powder and rubber powder on powder agglomeration and storage stability.
[0039] Figure 9 The figure shows the effect of co-pre-dispersion of ceramic powder and rubber powder on the swelling activation and heating uniformity of rubber powder.
[0040] Figure 10 This diagram illustrates the impact of the common pre-dispersion process on critical road performance.
[0041] in, Figure 2-6 In the text, Group A represents Comparative Example 1, Group B represents Comparative Example 2, Group C represents Comparative Example 3, and Group D represents Example 1.
[0042] Figure 8-10 In the text, E1 represents Comparative Example 4, E2 represents Comparative Example 5, E3 represents Comparative Example 6, and E4 represents Example 1. Detailed Implementation
[0043] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. After reading the present invention, any modifications of the present invention in various equivalent forms by those skilled in the art will fall within the scope defined by the appended claims.
[0044] Example 1
[0045] A method for preparing a far-infrared synergistic dispersion bio-based composite regenerator includes the following steps:
[0046] S1. Weigh 75g of rubber powder and 14g of silicon dioxide, and premix them at 500 r / min for 10 min to allow the silicon dioxide particles to enter the gaps between the rubber particles and obtain composite powder.
[0047] S2. Weigh 52.5g of tall oil fatty acid and 84g of epoxidized soybean oil, and mix them at 70℃ to form a pre-dispersion medium; wherein, the amount of tall oil fatty acid added accounts for 10% of its total mass, and the amount of epoxidized soybean oil added accounts for 60% of the total mass of the plasticizer;
[0048] S3. Add the composite powder to the pre-dispersion medium and pre-dispersion them together at 1500 r / min for 30 min to obtain the dispersion slurry.
[0049] S4. Weigh out the remaining tall oil fatty acid 472.5g, acetylsicit tributyl citrate 56g, antioxidant 10.5g and antioxidant 168 10.5g, mix at 60℃ for 20 min, then add the dispersion slurry, and continue stirring at 70℃ for 30 min to obtain the bio-based functional dispersion mother liquor.
[0050] S5. Heat 225g of base asphalt to 175℃, slowly add bio-based functional dispersion mother liquor, shear at 2000 r / min for 30 min at 165℃, and then keep warm at 155℃ for 30 min to allow the rubber powder to absorb oil and swell and achieve a particle size increase of about 1.58 times, thus obtaining far-infrared synergistic dispersion bio-based composite regenerator.
[0051] Among them, tall oil fatty acids, as a bio-based regenerated oil, are yellow transparent oily liquids with a resin acid content of 29.6 wt%, an unsaponifiable matter content of 6 wt%, a saponification value of 192 mgKOH / g, and an acid value of 186 mgKOH / g.
[0052] Antioxidant 1010, as a hindered phenolic primary antioxidant, is used to capture free radicals formed during thermo-oxidative aging and terminate free radical chain reactions; Antioxidant 168, as a phosphite auxiliary antioxidant, is used to decompose hydroperoxides formed during oxidation and reduce the generation of new reactive free radicals. The two are used in combination to exert a synergistic antioxidant effect of free radical capture and hydroperoxide decomposition.
[0053] A method for thermal recycling of asphalt includes the following steps: adding a far-infrared synergistic dispersion bio-based composite regenerator at a mass ratio of 5% to aged asphalt material, then heating it using a far-infrared heating device with a main emission band of 8-14μm; mixing the aged asphalt material and the far-infrared synergistic dispersion bio-based composite regenerator uniformly using a mixer under heating conditions of 160℃; adjusting the far-infrared radiation power during the heating and heat preservation stages, and adjusting the radiation power and mixing speed based on feedback from temperature acquisition points set at different locations in the mixing system, so that the temperature difference between the inside and outside of the mixing system does not exceed 5℃; during far-infrared radiation and dynamic mixing, the far-infrared radiation micro-region generates in-situ volume heating at the interface between rubber powder and aged asphalt, promoting the accelerated penetration and diffusion of bio-based regenerated oil into the interior of the rubber powder, causing the rubber powder to be reactivated secondary on the basis of primary oil absorption and swelling, thereby completing the recycling under continuous mixing conditions to obtain recycled asphalt.
[0054] Example 2
[0055] A method for preparing a far-infrared synergistic dispersion bio-based composite regenerator includes the following steps:
[0056] S1. Weigh 20g of rubber powder and 24g of alumina, and premix them at 300 r / min for 5 min to allow the alumina particles to enter the gaps between the rubber particles, thus obtaining a composite powder.
[0057] S2. Weigh 30g of vegetable oil fatty acid ester and 91.2g of epoxidized linseed oil, and mix them at 50℃ to form a pre-dispersion medium; wherein, the amount of vegetable oil fatty acid ester added accounts for 5% of its total mass, and the amount of epoxidized linseed oil added accounts for 60% of the total mass of the plasticizer;
[0058] S3. Add the composite powder to the pre-dispersion medium and pre-dispersion them together at 800 r / min for 20 min to obtain the dispersion slurry.
[0059] S4. Weigh out 570g of the remaining vegetable oil fatty acid ester, 60.8g of dioctyl sebacate, 12g of antioxidant 1010 and 12g of antioxidant 168, mix them at 60℃ for 20 min, then add the dispersion slurry, and continue stirring at 70℃ for 20 min to obtain the bio-based functional dispersion mother liquor.
[0060] S5. Heat 180g of base asphalt to 160℃, slowly add bio-based functional dispersion mother liquor, shear at 2000 r / min for 10 min at 140℃, and then keep warm at 140℃ for 10 min to allow the rubber powder to absorb oil and swell and achieve a particle size increase of about 1.65 times, thus obtaining far-infrared synergistic dispersion bio-based composite regenerator.
[0061] A method for thermal recycling of asphalt includes the following steps: adding a far-infrared synergistic dispersion bio-based composite regenerator at a mass ratio of 10% to aged asphalt material, then heating it with a far-infrared heating device with a main emission band of 8-14μm, mixing the aged asphalt material and the far-infrared synergistic dispersion bio-based composite regenerator evenly with a mixer under heating conditions of 120℃, and completing the recycling under continuous mixing conditions to obtain recycled asphalt.
[0062] Example 3
[0063] A method for preparing a far-infrared synergistic dispersion bio-based composite regenerator includes the following steps:
[0064] S1. Weigh 140g of rubber powder and 12g of titanium dioxide, and premix them at 1000 r / min for 30 min to allow the titanium dioxide particles to enter the gaps between the rubber particles and obtain composite powder.
[0065] S2. Weigh 90g of tall oil and 72g of epoxy fatty acid methyl ester, and mix them at 90℃ to form a pre-dispersion medium; wherein, the amount of tall oil added accounts for 20% of its total mass, and the amount of epoxy fatty acid methyl ester added accounts for 60% of the total mass of the plasticizer;
[0066] S3. Add the composite powder to the pre-dispersion medium and pre-dispersion them together at 2500 r / min for 60 min to obtain the dispersion slurry.
[0067] S4. Weigh out the remaining 360g tall oil, 48g epoxy fatty acid methyl ester, 9g antioxidant 1010 and 9g antioxidant 168, mix them at 80℃ for 30 min, then add the dispersion slurry, and continue stirring at 70℃ for 60 min to obtain the bio-based functional dispersion mother liquor.
[0068] S5. Heat 260g of base asphalt to 180℃, slowly add bio-based functional dispersion mother liquor, shear at 2000 r / min for 80 min at 180℃, and then keep warm at 170℃ for 60 min to allow the rubber powder to absorb oil and swell and achieve a particle size increase of about 1.78 times, thus obtaining far-infrared synergistic dispersion bio-based composite regenerator.
[0069] A method for thermal recycling of asphalt includes the following steps: adding a far-infrared synergistic dispersion bio-based composite regenerator to aged asphalt material at a mass ratio of 2.5%, then heating it with a far-infrared heating device with a main emission band of 8-14μm, and mixing the aged asphalt material and the far-infrared synergistic dispersion bio-based composite regenerator evenly with a mixer under heating conditions of 170℃, and completing the recycling under continuous mixing conditions to obtain recycled asphalt.
[0070] The principle of this invention is as follows: Figure 1 As shown, firstly, after premixing far-infrared ceramic powder and rubber powder, the ceramic microparticles enter the gaps between rubber powder particles and adhere to their surface. Subsequently, they are co-dispersed in a portion of bio-based recycled oil containing epoxy vegetable oil plasticizer. The far-infrared ceramic powder, through its surface polar sites such as hydroxyl groups and metal-oxygen bonds, undergoes non-covalent adsorption with carboxyl and ester groups in the bio-based recycled oil and epoxy and ester groups in the plasticizer, forming a surface-modified oil phase dispersion. This dispersion is enriched at the cross-linking shear interface between the bio-based oil phase and the rubber powder, constituting a far-infrared radiation micro-region.
[0071] After the pre-dispersed slurry is combined with the remaining oil phase and the matrix asphalt, the rubber powder absorbs the oil and undergoes primary oil absorption swelling, forming a primary oil absorption swelling gel state with a particle size of 1.2 to 1.8 times the original particle size. This gel state of rubber powder is distributed on the periphery of the far-infrared radiation micro-region, forming a core-shell response structure that can be reactivated.
[0072] During use, when far-infrared radiation in the 8–14 μm band is applied, the far-infrared ceramic powder enriched at the interface forms distributed thermal response micro-regions, generating in-situ volumetric heating at the interface. This promotes further diffusion of bio-based regenerated oil into the rubber powder and aged asphalt, enabling the rubber powder to undergo secondary activation based on primary swelling, thereby forming a complete synergistic swelling network. This network structure is composed of far-infrared radiation micro-regions, primary oil-absorbing and swollen gel-state rubber powder, and a continuous phase of asphalt / bio-based oil, effectively improving the compatibility, dispersion stability, and thermal response uniformity of the multiphase system.
[0073] Comparative Example 1
[0074] The preparation method of the regenerator includes the following steps: weigh 525g of tall oil fatty acid, 84g of epoxidized soybean oil, 56g of tributyl acetyl citrate, 10.5g of antioxidant 1010, 10.5g of antioxidant 168 and 225g of base asphalt, add them to the reaction vessel and mix them directly to obtain the regenerator.
[0075] Comparative Example 2
[0076] The preparation method of the regenerator includes the following steps: weigh 525g of tall oil fatty acid, 84g of epoxidized soybean oil, 56g of acetylsicitrin tributyl ester, 10.5g of antioxidant 1010, 10.5g of antioxidant 168, 225g of base pitch and 14g of silica, add them to the reaction vessel and mix them directly to obtain the regenerator.
[0077] Comparative Example 3
[0078] The preparation method of the regenerator includes the following steps: weigh 525g of tall oil fatty acid, 84g of epoxidized soybean oil, 56g of acetylsicitrin tributyl ester, 10.5g of antioxidant 1010, 10.5g of antioxidant 168, 225g of base asphalt and 75g of rubber powder, add them to a reaction vessel and mix them directly to obtain the regenerator.
[0079] Comparative Example 4
[0080] The preparation method of the regenerator includes the following steps: weigh 525g of tall oil fatty acid, 84g of epoxidized soybean oil, 56g of tributyl acetyl citrate, 10.5g of antioxidant 1010, 10.5g of antioxidant 168, 225g of base asphalt, 14g of silica and 75g of rubber powder, add them to a reaction vessel and mix them directly to obtain the regenerator.
[0081] Comparative Example 5
[0082] The preparation method of the regenerator includes the following steps: First, 14 g of silica is added to 525 g of tall oil fatty acid for pre-dispersion, then 75 g of rubber powder is added and mixed evenly, then 84 g of epoxidized soybean oil, 56 g of acetylsicitrin tributyl ester, 10.5 g of antioxidant 1010, 10.5 g of antioxidant 168 and 225 g of base asphalt are added and mixed evenly to obtain the regenerator.
[0083] Comparative Example 6
[0084] The preparation method of the regenerant includes the following steps:
[0085] (1) 75 g of rubber powder and 14 g of silica were premixed to obtain composite powder;
[0086] (2) Take 52.5g of tall oil fatty acids and mix with 84g of acetylated tributyl citrate to form a pre-dispersion medium;
[0087] (3) Add the composite powder to the pre-dispersion medium and pre-dispersion together to obtain a dispersion slurry;
[0088] (4) Take 472.5 g of tall oil fatty acid, 56 g of acetylsicitrin tributyl ester, 10.5 g of antioxidant 1010 and 10.5 g of antioxidant 168, mix them, and then add them to the dispersion slurry and mix well to obtain the bio-based functional dispersion mother liquor.
[0089] (5) Heat 225g of base asphalt and mix it with bio-based functional dispersion mother liquor. Keep it warm until the rubber powder has completed oil absorption and swelling to obtain far-infrared synergistic dispersion bio-based composite regenerator.
[0090] The method for preparing recycled asphalt includes the following steps: the recycling agent prepared in the above comparative examples 1-6 is added to the aged asphalt material at a mass ratio of 5%, and then heated using a far-infrared heating device. The aged asphalt material and the far-infrared synergistic dispersion bio-based composite recycling agent are stirred evenly using a mixer under heating conditions of 160°C, and the recycling is completed under continuous mixing conditions to obtain recycled asphalt.
[0091] I. Experimental Design
[0092] 1. Validation of synergistic effect
[0093] To verify the synergistic effect of far-infrared ceramic powder and rubber powder, four groups of regenerators were set up, namely the regenerator prepared in Example 1 and the regenerators prepared in Comparative Examples 1-3.
[0094] When the four groups of regenerators were used for thermal regeneration, the amount of regenerator added accounted for 5% of the total mass of the aged asphalt material. At the same time, the four groups of regenerators contained the same base oil phase (bio-based regenerated oil, plasticizer and anti-aging agent) components and dosages. Other components are shown in Table 1 below, to verify the comprehensive effect of molecular bridging interface coupling and synergistic swelling network.
[0095] Table 1: Objectives for Validating Synergistic Effects
[0096] Comparative Example 1 have none none Basic recovery function Comparative Example 2 have have none Far-infrared thermal response Comparative Example 3 have none have rubber elastic structure function Example 1 have have have Joint pre-dispersion and synergistic enhancement
[0097] 2. Joint pre-distributed verification
[0098] To verify the necessity of the specific process sequence in this invention, which involves "premixing rubber powder and far-infrared ceramic powder first, and then pre-dispersing them together in a bio-based oil phase containing epoxy plant oil plasticizers", four groups of regenerators were set up, namely the regenerator prepared in Example 1 and the regenerators prepared in Comparative Examples 1-3.
[0099] All four groups of regenerators maintained consistent amounts of bio-based oil, plasticizer, anti-aging agent, far-infrared ceramic powder, and rubber powder, as well as consistent total regenerator dosage and far-infrared thermal regeneration conditions. The only changes were the order of addition and dispersion of the ceramic powder and rubber powder, and whether the pre-dispersion medium contained epoxidized vegetable oil plasticizers. The validation objectives of the four groups of regenerators are shown in Table 2.
[0100] Table 2: Common Pre-Distribution Validation Objectives
[0101] Comparative Example 4 Ceramic powder and rubber powder are directly added to the oil-asphalt system. Without pre-dispersion, the powder is directly introduced into the high-viscosity system. Verify the risks of aggregation and segregation. Comparative Example 5 The ceramic powder is first pre-dispersed in the bio-based oil, and the rubber powder is added later. Only ceramic powder was pre-dispersed; rubber powder was not included in the co-pre-dispersion. Verification of the effect of ceramic powder pre-dispersion alone Comparative Example 6 The ceramic powder and rubber powder are first premixed, and then co-dispersed in a bio-based oil that does not contain epoxy vegetable oil plasticizers. The lack of epoxy and ester groups in interfacial wetting Verification of insufficient wetting of ordinary oil phase Example 1 The ceramic powder and rubber powder are first premixed, and then co-dispersed in a partially bio-based oil containing an epoxy vegetable oil plasticizer. Ceramic powder is enriched at the cross-linking shear interface of rubber powder, forming a surface-modified oil-phase dispersion. Verification of compatibility breakthroughs and formation of synergistic swelling networks
[0102] II. Performance Testing Based on Synergistic Effects
[0103] 1. Far-infrared heating efficiency and basic physical properties test
[0104] The heating efficiency of the recycling agents in Example 1 and Comparative Examples 1-3 was tested. The test method was as follows: the time required to heat the recycling agent to 160°C by mixing it with aged asphalt and using a far-infrared heating device.
[0105] The recycled asphalt from Example 1 and the recycled asphalt prepared using Comparative Examples 1 to 3 were subjected to basic physical property tests.
[0106] The basic physical properties were tested in accordance with the current "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG 3410-2025), with penetration, ductility and softening point tested using the methods specified in T0604-2011, T0605-2011 and T0606-2011, respectively; the sampling, temperature conditioning and testing conditions of each group of samples were kept consistent.
[0107] The calculation of the penetration recovery coefficient Rp and the ductility recovery coefficient Rd is as follows:
[0108] (1)
[0109] In equation (1), P reju P aged and P virgin These are the penetration values for recycled asphalt, aged asphalt, and unaged asphalt, respectively.
[0110] (2)
[0111] In equation (2), D reju D aged and D virgin These are the ductility of recycled asphalt, aged asphalt, and unaged asphalt, respectively.
[0112] The test results are shown in Table 3 below.
[0113] Table 3: Test Results of Heating Efficiency and Basic Performance
[0114] Comparative Example 1 12.6 44.2 64.2 20.6 0.540 0.290 Comparative Example 2 8.9 44.0 64.8 20.0 0.535 0.280 Comparative Example 3 12.2 40.8 70.4 18.5 0.460 0.254 Example 1 7.4 42.6 73.6 20.3 0.502 0.285
[0115] Combined with Table 3 and Figure 2 It can be seen that the time for Comparative Example 2 to reach 160℃ was shortened from 12.6 min to 8.9 min compared to Comparative Example 1, indicating that far-infrared ceramic powder mainly improves thermal response.
[0116] The softening point of Comparative Example 3 increased to 70.4 ℃, indicating that the rubber powder improved the structural support.
[0117] Example 1 reached 160 °C in just 7.4 min, with a softening point of 73.6 °C. Meanwhile, Rp and Rd remained at 0.502 and 0.285, respectively, indicating that the complete system after co-pre-dispersion achieved rapid heating and high-temperature structural compensation while restoring flexibility.
[0118] The results show that the present invention does not simply soften the oil, but achieves a synergistic balance between high-temperature support and flexible recovery.
[0119] 2. Multiple stress creep recovery test
[0120] The recycled asphalt from Example 1 and the recycled asphalt prepared using Comparative Examples 1 to 3 were subjected to multiple stress creep recovery tests.
[0121] The multiple stress creep recovery test was conducted according to the method specified in T0647-2025 of JTG 3410—2025, with a test temperature of 64 ℃ and stress levels of 0.1 kPa and 3.2 kPa, to obtain the irrecoverable creep compliance Jnr and recovery rate R; the same sample preparation and test procedures were used for each group.
[0122] The test results are shown in Table 4 below.
[0123] Table 4: Results of Multiple Stress Creep Recovery Tests
[0124] Comparative Example 1 1.68 3.10 18.5 7.0 Comparative Example 2 1.61 2.95 19.3 8.4 Comparative Example 3 0.72 1.16 48.6 31.2 Example 1 0.43 0.68 62.8 46.5
[0125] Combine Table 4 and Figure 3 It can be seen that the addition of far-infrared ceramic powder alone has limited direct improvement on MSCR; rubber powder significantly reduces the irreversible creep flexibility Jnr and significantly improves the recovery rate R.
[0126] In Example 1, Jnr at 3.2 kPa was 0.68 kPa. -1 The R value was 46.5%, which was 78.1% lower than that of the control group 1, while the R value increased by 39.5 percentage points.
[0127] This invention demonstrates that it can simultaneously reduce permanent deformation and improve elastic recovery under high stress conditions, and has good high-temperature stability.
[0128] 3. Bending beam rheometer test
[0129] The recycled asphalt from Example 1 and the recycled asphalt prepared using Comparative Examples 1 to 3 were subjected to bending beam rheometer tests.
[0130] The bending beam rheometer test was conducted according to the method specified in T0627-2011 of JTG 3410—2025. The creep stiffness S and creep rate m were measured at -18 ℃ and -24 ℃ for 60 s, respectively. The same sample preparation and testing procedures were used for each group.
[0131] The test results are shown in Table 5 below.
[0132] Table 5: Test results of bending beam rheometer
[0133] Comparative Example 1 182 0.346 294 0.305 Comparative Example 2 187 0.340 301 0.301 Comparative Example 3 213 0.318 332 0.286 Example 1 196 0.332 306 0.302
[0134] Combined with Table 5 and Figure 4 It can be seen that after adding rubber powder to Comparative Example 3, the low-temperature stiffness increased and the creep rate decreased.
[0135] Compared with Comparative Example 3, Example 1 reduced the creep stiffness S from 332 MPa to 306 MPa and increased the creep rate m from 0.286 to 0.302 at -24℃, indicating that the combined pre-dispersion and interfacial wetting effects can reduce local agglomeration or excessive stiffening of rubber powder, demonstrating that while strengthening at high temperatures, stiffening at low temperatures is significantly alleviated.
[0136] 4. Pull-out test of asphalt-aggregate interface
[0137] The recycled asphalt from Example 1 and the recycled asphalt prepared using Comparative Examples 1 to 3 were subjected to asphalt-aggregate interface pull-out tests.
[0138] During the experiment, granite aggregate substrates with dimensions of 50 mm × 50 mm × 10 mm were used. After grinding, cleaning, and drying, the recycled asphalt prepared in Example 1 and Comparative Examples 1-3 was uniformly coated onto the substrates, with the coating thickness controlled at 0.50 mm ± 0.05 mm. A pull-out head with a diameter of 20 mm was used, and the substrates were cured at 25 ℃ for 24 h. Three parallel specimens were set up for each group. The specimens were then fixed on the pull-out testing machine, with the axis of the pull-out head aligned with the loading direction. A tensile force was applied vertically upward at a constant loading rate of 0.70 MPa / s ± 0.05 MPa / s at 25 ℃ until the specimen completely failed. The maximum load Pmax at failure was recorded, and the maximum pull-out strength POTS was calculated using the following formula:
[0139] (3)
[0140] In equation (3), Pmax is the maximum load for pull-out failure, and A is the effective pull-out area.
[0141] Meanwhile, parallel specimens were immersed in a 40 ℃ water bath for 24 h, and then subjected to pull-out tests under the same conditions. The maximum pull-out strength POTS24 h after immersion was recorded and compared with the dry state POTSdry. The strength retention rate BSR24 after immersion was calculated using the following formula:
[0142] (4)
[0143] After the pull-out test, images of the fracture surface were acquired. The residual asphalt area (Aresidual asphalt) and the total effective analytical area (Atotal) on the fracture surface were statistically analyzed using image analysis software. The cohesive dominant failure area fraction (Ac) was calculated using the following formula:
[0144] (5)
[0145] Each group of experiments should have at least 5 parallel specimens, and the average value of the valid data should be taken as the final experimental result.
[0146] The test results are shown in Table 6 below:
[0147] Table 6: Pull-out test of asphalt-aggregate interface
[0148] Comparative Example 1 1.10 0.72 65.5 57 Comparative Example 2 1.13 0.74 65.5 59 Comparative Example 3 1.28 0.91 71.1 66 Example 1 1.41 1.15 81.6 78
[0149] Combined with Table 6, Figure 5 and Figure 7 It can be seen that in Example 1, the dry POTS at 25 ℃ reached 1.41 MPa, and after immersion in water for 24 hours, it was still 1.15 MPa. The BSR24 was 81.6% and the Ac was 78%, indicating that the complete system simultaneously improves the wet bearing capacity and the residual area of asphalt on the fracture surface, causing the failure mode to shift towards cohesive failure.
[0150] III. Quantitative Analysis of Synergistic Effects
[0151] To quantitatively characterize the combined effect of far-infrared ceramic powder and rubber powder, four two-factor controls were set up: Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.
[0152] For any performance index Z, without any interaction, the theoretical value of the simple superposition in Example 1 is:
[0153] (6)
[0154] In equation (6), For any performance index in Comparative Example 2, the measured value is given. For any performance index in Comparative Example 3, the measured value is given. The measured value is for any performance index of Comparative Example 1.
[0155] For metrics such as time to reach target temperature, Jnr, and S, where lower values generally indicate better performance, the synergistic reduction factor is:
[0156] (7)
[0157] In equation (7), The measured value is any performance index of Example 1.
[0158] For metrics such as R, m, BSR, and Ac, where higher values generally indicate better performance, the synergistic improvement coefficient is:
[0159] (8)
[0160] In equation (8), The measured value is any performance index of Example 1.
[0161] When the corresponding synergy coefficient is greater than 0, it indicates that the performance improvement of Example 1 exceeds the linear superposition of the effects of the two factors alone.
[0162] The results of the quantitative analysis are shown in Table 7 below.
[0163] Table 7: Quantitative Analysis Results of Synergistic Effect
[0164] Time to reach 160 ℃ / min 8.50 7.40 12.9 reduce <![CDATA[Jnr0.1 / kPa -1 ]]> 0.65 0.43 33.8 reduce <![CDATA[Jnr3.2 / kPa -1 ]]> 1.01 0.68 32.7 reduce R0.1 / % 49.4 62.8 27.1 improve R3.2 / % 32.6 46.5 42.6 improve S-18℃ / MPa 218 196 10.1 reduce S-24℃ / MPa 339 306 9.7 reduce m-18℃ 0.312 0.332 6.4 improve m-24℃ 0.282 0.302 7.1 improve Soaked in water 24hPOTS / MPa 0.93 1.15 23.7 improve BSR24 / % 71.1 81.6 14.8 improve Ac / % 68 78 14.7 improve
[0165] Combined with Table 7 and Figure 6 As can be seen from the results, Example 1 exhibits positive synergy across multiple performance domains, including thermal response, high-temperature permanent deformation, high-temperature recovery, low-temperature stiffness and relaxation, wet pull-out strength, and failure modes. Specifically, the synergistic reduction coefficient of Jnr3.2 is 32.7%, and the synergistic improvement coefficient of R3.2 is 42.6%, indicating that the combined effect of the pre-dispersed far-infrared ceramic powder and rubber powder in the complete system exceeds the simple superposition of their individual effects.
[0166] IV. Performance Testing Based on Common Pre-Dispersion
[0167] 1. Compatibility and storage stability tests
[0168] The regenerators prepared in Example 1 and Comparative Examples 4-6 were subjected to tests to determine the powder agglomeration area ratio, 48-h segregation rate, 24-h viscosity change rate, and softening point difference, respectively, in order to investigate the effects of different pre-dispersion processes on the powder dispersion uniformity and storage stability of the composite regenerator.
[0169] The method for determining the powder agglomeration area ratio is as follows: A thin layer with a thickness of 1.0 mm ± 0.1 mm is prepared from the sample, and microscopic images are acquired under 100× magnification and the same illumination conditions. Five fields of view are randomly acquired for each parallel sample, and three parallel samples are set up for each group. The powder agglomeration area is divided using the same threshold. The percentage of the total area of the agglomeration area to the total area of the effective field of view is expressed as the average value. Storage stability is determined according to the segregation test of polymer-modified bitumen specified in T0661-2025 of JTG 3410—2025. After storing the sample at 163 ℃ ± 5 ℃ for 48 h, the softening points of the upper and lower layers are measured. The difference in softening points is the absolute value of the difference between the upper and lower layers. The segregation rate at 48 h is the percentage of the ratio of the softening point difference to the average softening point of the upper and lower layers. The 24-hour viscosity change rate was determined using the rotational viscosity method (T0619-2025) in JTG 3410-2025. The initial viscosity and the viscosity after 24 hours of storage were measured at 135℃ under the same rotor conditions, and the difference was expressed as a percentage of the initial viscosity. Sampling locations, storage temperatures, testing temperatures, and image processing parameters were kept consistent across all groups. The experimental results are shown in Table 8.
[0170] Table 8: Results of tests on compatibility and storage stability of co-predisposition
[0171] Comparative Example 4 17.8 7.4 14.0 5.0 Comparative Example 5 11.2 5.0 9.5 3.2 Comparative Example 6 8.6 3.6 7.1 2.4 Example 1 4.6 1.8 3.9 1.3
[0172] Combined with Table 8 and Figure 8 It can be seen that Example 1 had the lowest agglomeration area ratio, 48-hour segregation rate, 24-hour viscosity change rate, and softening point difference, which were 4.6%, 1.8%, 3.9%, and 1.3℃, respectively, with a softening point difference of less than 2.5℃. Compared with Comparative Example 4, Example 1 showed a 74.2% reduction in agglomeration area ratio, a 75.7% reduction in 48-hour segregation rate, a 72.1% reduction in 24-hour viscosity change rate, and a 74.0% reduction in softening point difference. Compared with Comparative Example 6, which was a co-dispersion process without epoxidized vegetable oil plasticizers, Example 1 still showed further improvement.
[0173] Therefore, the co-pre-dispersion process containing epoxy plant oil plasticizers of the present invention can simultaneously improve the uniformity of powder dispersion and the storage stability of composite regenerators. Epoxy plant oil plasticizers are key components in forming surface-modified oil phase dispersions and molecularly bridged interface coupling structures of ceramic powders.
[0174] 2. Rubber powder swelling activation and far-infrared heating uniformity test
[0175] The regenerants prepared in Examples 1 and Comparative Examples 4-6 were tested for 60 min swelling rate and particle size growth factor of rubber powder under the same mass ratio, temperature, far-infrared radiation conditions, and shear conditions. For swelling rate determination, 10.00 g of initial rubber powder was weighed for each parallel sample. After reacting for 60 min, the rubber powder was recovered using a 100-mesh metal sieve and gently pressed three times with oil-absorbing paper to remove surface free oil. The percentage increase in mass of recovered rubber powder relative to the initial mass was used as the 60 min swelling rate. Particle size growth factor was analyzed using 100× optical microscopy. The median particle size (D50) of at least 200 rubber powder particles was counted before and after the reaction, and expressed as the ratio of D50 after 60 min to the initial D50. Three parallel samples were set up for each group, and the average value was taken.
[0176] The rejuvenating agents prepared in Examples 1 and Comparative Examples 4-6 were mixed with equal masses of aged asphalt material. Each time, 500 g of the mixture was placed in a 1000 mL cylindrical metal container. Identical temperature sensors were placed along the central axis of the mixture and 5 mm from the inner wall of the container, with the same insertion depth and measurement height. Heating was performed under identical far-infrared emission band, power, and mixing speed conditions. The time required for the central measuring point to first reach 160 °C was recorded, and the absolute value of the temperature difference between the central measuring point and the near-wall measuring point after 10 minutes of heating was taken as the 10-minute internal and external temperature difference. Three parallel samples were set up for each group, and the average value was taken.
[0177] The method for determining the 10-minute internal and external temperature difference is as follows: In a container filled with the mixture, internal and external temperature sensors are installed at the center of the mixture and near the surface of the container's inner wall, respectively. The positions and insertion depths of each measuring point are fixed. Timing is started simultaneously when the far-infrared heating device is turned on, maintaining the same dynamic mixing regime. The temperatures at both measuring points are continuously recorded using a data acquisition system. When heating reaches 10 minutes, the internal and external temperatures are read simultaneously, and the absolute value of the difference between them is taken as the 10-minute internal and external temperature difference.
[0178] The test results are shown in Table 9 below.
[0179] Table 9: Test results of the effect of co-predisposition on the swelling and far-infrared heating uniformity of rubber powder
[0180]
[0181] Combining Table 9 and Figure 9 It can be seen that the rubber powder of Example 1 has the highest swelling rate and particle size growth factor at 60 min, which are 33.1% and 1.58, respectively. At the same time, the time required to reach 160 °C and the internal and external temperature difference are the lowest, which are 7.4 min and 4.8 °C, respectively, with the internal and external temperature difference not exceeding 5 °C.
[0182] Compared with Comparative Example 4, Example 1 showed a 14.7 percentage point increase in swelling rate, an increase in particle size growth factor from 1.22 to 1.58, a 15.9% reduction in time to reach 160 °C, and a 60.0% reduction in internal and external temperature difference.
[0183] As shown in Table 9, under the test conditions, Example 1 showed a shorter time to reach 160 ℃ and a smaller temperature difference between the inside and outside of the sample compared to Comparative Example 4. At the same time, the swelling rate and particle size growth factor of the rubber powder at 60 min were increased. This indicates that the pre-dispersion of ceramic powder and rubber powder together with epoxy vegetable oil plasticizer is beneficial to improving the uniformity of far-infrared heating and promoting the oil absorption and swelling of rubber powder.
[0184] 3. Critical road performance test
[0185] The recycled asphalt prepared in Example 1 and Comparative Examples 4-6 were evaluated for high-temperature elastic recovery and wet interface retention properties, respectively. Test parameters included the unrecoverable creep compliance Jnr3.2 at 64℃ and 3.2 kPa, the recovery rate R3.2, the strength retention rate BSR24 after 24 hours of immersion in water, and the cohesive-dominated failure area fraction Ac.
[0186] The test results are shown in Table 10 below.
[0187] Table 10: Test Results of Critical Road Performance
[0188] Comparative Example 4 0.94 35.8 72.4 67 Comparative Example 5 0.84 39.7 75.3 70 Comparative Example 6 0.76 42.5 78.2 73 Example 1 0.68 46.5 81.6 78
[0189] Combining Table 10 and Figure 10 As can be seen, as the dispersion process gradually changes from direct addition to co-pre-dispersion with epoxy vegetable oil plasticizers, the high-temperature deformation resistance, high-temperature elastic recovery, and wet interface retention properties of the system all show a continuous improvement trend.
[0190] In Example 1, Jnr3.2 was 0.68 kPa. -1 The R3.2 was 46.5%, the BSR24 was 81.6%, and the Ac was 78%. Compared with Comparative Example 4, the Jnr3.2 of Example 1 decreased by 27.7%, the R3.2 increased by 10.7 percentage points, the BSR24 increased by 9.2 percentage points, and the Ac increased by 11 percentage points.
[0191] Therefore, the above experimental results support the following interaction relationship: epoxy vegetable oil plasticizer, bio-based oil and ceramic powder together form a polar-nonpolar compatible interface, and far-infrared ceramic powder plays a role in spatial separation and local thermal response enhancement between rubber powder particles, so that the rubber powder is more uniformly wetted, dispersed and swollen in the oil phase and asphalt phase; compared with Example 1, the comparative examples of direct addition, pre-dispersion of ceramic powder only or omission of epoxy vegetable oil plasticizer all showed different degrees of deterioration in terms of agglomeration, segregation, temperature uniformity and road performance indicators, indicating that a specific dispersion sequence is conducive to the formation of a stable microphase structure.
Claims
1. A far-infrared synergistic dispersion bio-based composite regenerator, characterized in that, The product comprises the following components in parts by weight: 39-60 parts by weight of bio-based recycled oil, 3-16 parts by weight of plasticizer, 0.6-2.4 parts by weight of anti-aging agent, 0.6-2.4 parts by weight of far-infrared ceramic powder, 13-36 parts by weight of base asphalt, and 2-14 parts by weight of rubber powder; wherein the plasticizer includes epoxy vegetable oil plasticizer.
2. The far-infrared synergistic dispersion bio-based composite regenerator according to claim 1, characterized in that: The epoxidized vegetable oil plasticizer is selected from one or more of epoxidized soybean oil, epoxidized linseed oil, and epoxidized fatty acid methyl esters.
3. The far-infrared synergistic dispersion bio-based composite regenerator according to claim 1, characterized in that: The plasticizer also includes cold-resistant ester plasticizers, which are selected from one or more of acetylated tributyl citrate, tributyl citrate, dioctyl sebacate, and dioctyl adipate; the epoxy vegetable oil plasticizer accounts for 30-100% of the total mass of the plasticizer.
4. The far-infrared synergistic dispersion bio-based composite regenerator according to claim 1, characterized in that: The bio-based recycled oil is selected from one or more of tall oil-based bio-based oils, waste edible oil modified products, vegetable oils, vegetable oil fatty acid esters, and biomass pyrolysis oil modified products; the tall oil-based bio-based oil is selected from one or more of tall oil, distilled tall oil, tall oil fatty acids, tall oil pitch, and tall oil pitch modified products.
5. The far-infrared synergistic dispersion bio-based composite regenerator according to claim 1, characterized in that: The far-infrared ceramic powder is selected from one or more of the following minerals: silicon dioxide, aluminum oxide, zirconium oxide, titanium dioxide, iron oxide, manganese oxide, magnesium oxide, calcium oxide, cerium oxide, zircon sand, feldspar, maifanite, cordierite, and spinel.
6. The far-infrared synergistic dispersion bio-based composite regenerator according to claim 1, characterized in that: The anti-aging agent includes a primary antioxidant and a secondary antioxidant; the primary antioxidant is a hindered phenolic antioxidant, and the secondary antioxidant is a phosphite antioxidant and / or a thioester antioxidant.
7. The method for preparing the far-infrared synergistic dispersion bio-based composite regenerator according to any one of claims 1-6, characterized in that, Includes the following steps: S1. Premix rubber powder with far-infrared ceramic powder to obtain composite powder; S2. Mix a portion of the bio-based recycled oil with a portion of the plasticizer to form a pre-dispersion medium; S3. Add the composite powder to the pre-dispersion medium and pre-dispersion together to obtain a dispersion slurry; S4. Take the remaining amount of bio-based recycled oil, the remaining amount of plasticizer and anti-aging agent, mix them, and then add them to the dispersion slurry and mix well to obtain the bio-based functional dispersion mother liquor. S5. After heating the base asphalt, mix it with the bio-based functional dispersion mother liquor and keep it warm until the rubber powder has completed oil absorption and swelling. The rubber powder absorbs oil and swells to 1.2 to 1.8 times its original particle size to obtain a far-infrared synergistic dispersion bio-based composite regenerator.
8. The preparation method of the far-infrared synergistic dispersion bio-based composite regenerator according to claim 7, characterized in that: In step S2, the amount of bio-based recycled oil added accounts for 5-20% of its total mass, and the amount of plasticizer added in step S2 accounts for 30-60% of the total mass of plasticizer, and the plasticizer added in step S2 is an epoxy vegetable oil plasticizer.
9. The preparation method of the far-infrared synergistic dispersion bio-based composite regenerator according to claim 7, characterized in that: In step S1, stir at a speed of 300-1000 r / min for 5-30 min to complete the premixing; The temperature of the pre-dispersed medium in step S2 is 50℃~90℃; In step S3, the mixture is stirred at a speed of 800–2500 r / min for 20–60 min to complete the co-pre-dispersion. In step S5, the base asphalt is heated to 160-180°C, and the bio-based functional dispersion mother liquor is slowly added. The mixture is then stirred or sheared at 140-180°C for 10-80 minutes and kept at 140-180°C for 10-60 minutes.
10. A method for thermal recycling of asphalt, characterized in that, The process includes the following steps: adding the far-infrared synergistic dispersion bio-based composite regenerator according to any one of claims 1 to 6 to the aged asphalt material at a mass ratio of 2.5% to 10%, then heating it with a far-infrared heating device with a main emission band of 8 to 14 μm, stirring the aged asphalt material and the far-infrared synergistic dispersion bio-based composite regenerator evenly under heating conditions of 120°C to 170°C, and completing the regeneration under continuous stirring conditions.
